2018
DOI: 10.3390/ijms19030824
|View full text |Cite
|
Sign up to set email alerts
|

3′-UTR Polymorphisms of MTHFR and TS Associated with Osteoporotic Vertebral Compression Fracture Susceptibility in Postmenopausal Women

Abstract: Postmenopausal osteoporosis is one of the most prominent diseases in postmenopausal women and it is increasing in prevalence with the aging population. Furthermore, osteoporosis and osteoporotic vertebral compression fractures (OVCFs) are related to mortality and decreased quality of life. Therefore, searching for biomarkers that are able to identify postmenopausal women who are at high risk of developing OVCFs is an effective strategy for improving the quality of life of patients and alleviating social and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…MTHFR polymorphism C667 T could also be involved in the increase of osteoporotic fracture incidence [181], and a recently published meta-analysis showed an association between MTHFR C667 T polymorphism and reduced bone mineral density in the lumbar spine and femoral neck in Caucasians, post-menopausal women, and men, and with total BMD in women [185]. Ahn et al [186] reported an association in 301 postmenopausal women between osteoporotic vertebral compression fractures and MTHFR and TS gene polymorphisms in the 3 -UTR region. Concerning the effect of supplementation, a systematic review with meta-analysis [187] concluded that vitamin B12 status may be associated with fracture risk, and evidence for an association between folate status and fracture risk is scarce.…”
Section: Osteoporosismentioning
confidence: 99%
“…MTHFR polymorphism C667 T could also be involved in the increase of osteoporotic fracture incidence [181], and a recently published meta-analysis showed an association between MTHFR C667 T polymorphism and reduced bone mineral density in the lumbar spine and femoral neck in Caucasians, post-menopausal women, and men, and with total BMD in women [185]. Ahn et al [186] reported an association in 301 postmenopausal women between osteoporotic vertebral compression fractures and MTHFR and TS gene polymorphisms in the 3 -UTR region. Concerning the effect of supplementation, a systematic review with meta-analysis [187] concluded that vitamin B12 status may be associated with fracture risk, and evidence for an association between folate status and fracture risk is scarce.…”
Section: Osteoporosismentioning
confidence: 99%
“…Patients with osteoporosis can suffer from fracture when subjected to low-energy shock due to the increased bone fragility, and the fractures are often found in the pelvis, vertebrae, hip, and proximal humerus, clinically known as osteoporotic vertebral compression fracture (OVCF) [9]. The incidence of OVCF in women is significantly higher than that in men, especially in postmenopausal women, which may be associated with changes in estrogen levels of postmenopausal women [10]. The clinical manifestations of OVCF are mainly unbearable pain and inability to walk, which severely affects the quality of life of patients, and some patients with OVCF have mental disorder and venous thrombosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we should consider the possible changes of analyzed genes due to change in miRNA action because we investigated SNPs located in 3´–UTR of B vitamin–related genes. Genetic variation in the 3´–UTR can affect gene expression by interfering with miRNA binding [ 12 , 37 , 38 ]. Polymorphisms residing within the miRNA–binding site of the target genes may have their own disease onset effect, but changes in the miRNA binding efficiency also has to be considered [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single nucleotide polymorphism (SNPs) in methylenetetrahydrofolate reductase ( MTHFR 677 C>T) has been shown to be associated with BMD [ 10 , 11 ]. Recently, it was also reported that SNPs in the 3´ untranslated regions (UTRs) of MTHFR (2572 C>A) and thymidylate synthase (1100 C>T) are associated with the prevalence of osteoporosis and osteoporotic vertebral compression fractures (OVCFs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%